Implementasi Proses Desain Interaksi Pada Telepon Genggam Untuk Anak-anak Berbasis Arduino Nano - Oktaviany Setyowati; Hurriyatul Fitriyah; Rizal Maulana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
A handphone is a two-way telecommunication tool that can be so easy to bring it anywhere and has the ability to send a voice message. Many kind user of this communication tool, from children to adults. Children are sometimes beyond the normal usage limits and have negative impact. Children can open content that is not appropriate for their age resulting in their social behavior. Because of this case, in this research to simplify and maintain usage of a handphone for children which create based on several stages of interaction design that are: â€œwhat is wantedâ€, â€œanalysisâ€, â€œdesign prototypeâ€, and â€œimplementâ€. This handphone will be made without screen, there are just 4 buttons with each functions. Each button equipped with an attractive emoticon that usually used in any smartphones currently. The functions are for calling your father, mother, teacher and received a call. In terms of handphone usability testing with Likert scale involving 30 children kindergarten, usability category, satisfaction, ease to use and easy to learn score average 4. Testing keypad by involving 2 kindergarten teachers stated that teachers find it difficult to use this tool because there is no screen available when typing, and they are difficult to understand serial monitor on Arduino IDE.